A Giant Protopaleodictyon from the Middle Cambrian of Western Canada. Issue 3 (3rd July 2019) - Morgan, Chad A.; Henderson, Charles M.; Pratt, Brian R.
Abstract: A new ichnospecies of Protopaleodictyon Książkiewicz, 1958, Pr. aitkeni isp. n., is named from material recovered from the mid–Cambrian Stephen–Eldon formation transition in Banff National Park, Alberta, Canada. Specimens occur in convex hyporelief on the sole of a dolomitic lime mudstone bed, and exhibit straight to gently curving strands with a 'zigzag' shape up to 45 cm in length. Strands are fairly regular, with branching angles ranging from 110 ° to 120 ° . Branch segments forming the strand are approximately the same length and produce strands with open and occasionally closed hexagonal polygons arranged alternatively along the specimen's axis. Hexagons are 25–40 mm wide and string widths are 5–10 mm. The dimensions of Pr. aitkeni are large compared to other ichnospecies of the ichnogenus and graphoglyptids in general. The host interval is interpreted to have been deposited in a relatively shallow-water environment in the interior of a carbonate platform, contrasting with the deeper siliciclastic settings in which younger examples of the ichnogenus typically occur. This occurrence further supports the hypothesis that graphoglyptid ethology initially developed in shallow shelf environments before shifting into deeper facies over geologic time.